Buku Ajar Bahasa Arab Kelas 4 Madrasah Ibtidaiyah: Analisis Standar 5C ACTFL - Muslimah, Kiki Cahya; Ainin, Moh.; Sanusi, Anwar (Universitas Negeri Jakarta, 2022)
5C’s of the American Council on Teaching of Foreign Languages ​​(ACTFL) is a standard in teaching foreign languages ​​in the United States, which emphasizes five important and interrelated things in teaching foreign languages; communication, culture, connections, comparisons, and communities. The 5C’s of ACTFL are used as a guide in creating a curriculum that can enable students to develop various skills, gain insights from other cultures, connect language skills acquired with other scientific fields, develop insights by comparison, and participate in a multilingual society. This study aim to answer the question of the results of the ACTFL 5C’s standard analysis in the Arabic textbooks for class 4 in Madrasah Ibtidaiyah published by the Ministry of Religion of the Republic of Indonesia. This type of research is library research conducted with research objects or library data collection. The analysis found that the Arabic textbook complies with the ACTFL 5C’s standard. The Arabic textbook can optimize learning Arabic for elementary school; Madrasah Ibtidaiyah class 4. In detail, the percentage of the ACTFL 5C’s standard is 31% communication, 25% cultures, 22% connections, 14% comparisons, and 8% communities.